2019
DOI: 10.18203/issn.2454-5929.ijohns20195583
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxic effect of anti-tubercular treatment on multi-drug resistant tuberculosis patient

Abstract: <p class="abstract"><strong>Background:</strong> Multi-drug resistant tuberculosis (MDR-TB) is defined as tuberculosis caused by <em>Mycobacterium tuberculosis</em> resistant in vitro to the effects of isoniazid and rifampicin, with or without resistance to any other drugs. Regimen for MDR-TB<strong> </strong>comprises of 6 drugs - kanamycin, levofloxacin, ethionamide, pyrazinamide, ethambutol and cycloserine during 6-9 months of the intensive phase and 4 drugs levoflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In the drug-resistant group, seventeen ( 17) participants (44.7%) met the criteria for threshold shift after three (3) months whereas only one (1) participant (2.6%) met these criteria in the drug-susceptible group. Jain et al found similar threshold shifts in their study of patients on treatment for drug-resistant tuberculosis as majority of their patients (85.7%) had bilateral threshold shifts at the higher frequencies [23]. Threshold shift appears to be a consistent audiometric finding among patients treated for drug-resistant tuberculosis for a prolonged duration.…”
Section: Discussionmentioning
confidence: 60%
“…In the drug-resistant group, seventeen ( 17) participants (44.7%) met the criteria for threshold shift after three (3) months whereas only one (1) participant (2.6%) met these criteria in the drug-susceptible group. Jain et al found similar threshold shifts in their study of patients on treatment for drug-resistant tuberculosis as majority of their patients (85.7%) had bilateral threshold shifts at the higher frequencies [23]. Threshold shift appears to be a consistent audiometric finding among patients treated for drug-resistant tuberculosis for a prolonged duration.…”
Section: Discussionmentioning
confidence: 60%